Plano de ações estratégicas para o enfrentamento da mortalidade materna e perinatal na Unidade Básica de Saúde Indígena São Marcos - Santos, Arielle Carlos Costa dos (2024)
Introduction: Maternal and perinatal mortality represent a significant challenge to public health, especially in indigenous populations. Health indicators reveal an alarming panorama in the São Marcos Indigenous Health Basic Unit, evidencing the fragility in maternal and perinatal health. The Maternal Mortality Ratio (MMR) in São Marcos is unacceptably high, 18.3 times higher than the rate accepted by the WHO, while the Perinatal Mortality Rate in São Marcos is 6.52 times higher than the national average. Given this scenario, this study proposes the construction of a strategic action plan to address maternal and perinatal mortality in the population served by the São Marcos UBSI. Objective: To build a strategic action plan to address maternal and perinatal mortality to reduce mortality in the population of the São Marcos Indigenous Health Basic Unit. Materials and Methods: The research and development project aims to intervene in the reality studied. As for its purposes, it is exploratory, descriptive and interventionist. The means used to achieve the proposed objective is action research. The approach is qualitative. Carlos Matus' Situational Strategic Planning was the theoretical and methodological framework used to construct the Confrontation Plan based on participatory planning workshops using principle-based negotiation to reach consensus and the Two-Eyed approach for a more holistic and culturally appropriate approach. Results: Health professionals, representatives of the Catholic Church, midwives, female leaders and vice chief participated collaboratively in the workshops, totaling 32 participants. The construction process was divided into stages that involved Problem Analysis, Problem Explanation, and Intervention Design. Monitoring, the last stage, will take place in 2025 after the implementation of the plan. In the first workshop, the 32 problems that affect women's health were listed. The problems of food and financial insecurity, lack of humanized care in hospitals and interpreters of the Xavante language, lack of counter-referral, high incidence of perinatal deaths due to causes sensitive to primary care, difficulty in organizing medical records and health records, poor basic sanitation, difficulty in accessing imaging exams during prenatal care, men's resistance to the use of contraceptive methods by women, late start of prenatal care and low early recruitment of pregnant women by the team, insufficient home visits carried out by Indigenous Health Agents, lack of qualified human resources for prenatal care were prioritized. Conclusion: This research and development project made it possible to construct a Strategic Action Plan to address maternal and perinatal mortality in the São Marcos micro-area. The magnitude of this study goes beyond the identification of unfavorable outcomes, highlighting the urgent need to improve strategic actions aimed at reducing maternal and perinatal mortality rates.